(untitled) (Journal of Information Technologies in Education (ITE), 2010)
The article presents methods of learning which to be used efficiently require the usage of capabilities of modern information and communication technologies. Introduction of the described methods into education allows implementing in practice the ideas of development of pedagogic and helps forming information culture of school leavers.